ASSOCIATION BETWEEN CARDIAC LESION AND OTHER CLINICAL MANIFESTATIONSOF ANKYLOSING SPONDYLITIS - Alla Aleksandrovna Godzenko; A G Bochkova; O A Rumyantseva; Yu O Korsakova; N V Bunchuk; Alla Aleksandrovna Godzenko; A G Bochkova; O A Rumyantseva; Yu O Korsakova; N V Bunchuk (Научно-практическая ревматология)
Objective: to study associations between the lesion of the heart and aorta and other clinical manifestations and the characteristics of ankylosing spondylitis (AS). Subjects and methods. Three hundred and forty-four patients under 60 years of age with a valid diagnosis of AS without concomitant heart disease, followed up at the Research Institute of Rheumatology, Russian Academy of Medical Sciences, in 2005-2008, were examined. Of them, 64 (18.6%) patients had at least one attack of uveitis during the disease; 280 had never uveitis. During the disease, peripheral arthritis occurred in 160 (46.5%) patients; 184 (53.5%) had axial AS. All the patients underwent ECG; 101 had EchoCG (27 with uveitis and 74 without uveitis, 63 with arthritis and 38 without arthritis). Results. Forty-four patients were found to have cardiac conduction disturbances (atrioventricular or left bundle-branch block); of them 14 (31.8%) and 30 (68%) had uveitis and peripheral arthritis, respectively. Out of the 300 individuals without conduction disturbances, 50 (16.7%) and 130 (43%) had the above conditions (p = 0.01 and 0.003, respectively). Cardiac structural changes (aortic thickening/dilatation, subaortic bump, aortic and/or mitral leaflet thickening) were revealed in 45 patients; among them 21 (46.7%) and 34 (75%) had uveitis and arthritis, respectively; of the 56 patients without EchoCG changes, 6 (10.7%) and 29 (51%) had the above conditions (p = 0.0001 and 0.02, respectively). On the other hand, conduction disturbances were noted in 15 (23.4%) of the 64 patients with uveitis and in 29 (10.3%) of the 280 patients without this condition; p = 0.006; in 30 (19%) of the 160 patients with peripheral arthritis and in 14 (7.6%) of the 180 patients without arthritis; p = 0.003. Aortic and valvular changes were detected in 16 (59.2%) of the 27 patients with uveitis and in 28 (37.8%) of 74 without this condition; p = 0.04; in 36 (57%) patients with arthritis and in 9 (23%) of the 38 without arthritis; p = 0.018. There were no significant differences in the parameters of inflammatory activity between the groups. Conclusion. In patients with AS, cardiac lesion was significantly more frequently in the presence of uveitis and peripheral arthritis; uveitis and peripheral arthritis were significantly more common in patients with AS-induced cardiac changes.